P148 Female genital mutilation – when do you call 101?. (8th June 2017) - Seneviratne, Kanch; Boog, Katie; Cooper, Susan; Munatsi, Shereen; Carlin, Elizabeth
Abstract : Introduction: Reporting cases of FGM in those aged under 18 years became mandatory in 2015. Protecting those who have been affected and safeguarding those at potential risk is paramount. Aims: To evaluate staff knowledge of FGM and the volume of FGM seen in two neighbouring sexual health services. Methods: Clinicians were asked to complete a questionnaire assessing their knowledge and understanding of the FGM care pathway. Case notes of women with a FGM code since its introduction in 2014 were reviewed. Results: Forty-six clinicians completed the questionnaire Twenty-two women, aged 24–59 years, were identified with a FGM code, 91% were of Black African ethnicity. Overall, 74% of staff were aware of the need to ask about other daughters, social services referral and police contact. A quarter were unable to summarise appropriate action plans, of particular concern in this group were those who felt they understood the care pathway. Only a fifth stated that they coded genital piercings as FGM. Discussion: There is a clear knowledge gap in actions and coding required in relation to FGM. Over 80% staff recognised this and requested training. Plans are underway to deliver this and close the gap as a priority. A flow chart for quick reference has been developed and will be available at the conference.